Pengaruh Leader Member Exchange dan Pengembangan Karir terhadap Organizational Citizenship Behavior pada PT Andhika Pratama Jaya Abadi - Try Firmansyah Ginting; Tapi Rondang Ni Bulan; Bunga Aditi (Jurnal Ilman: Jurnal Ilmu Manajemen, 2021)
this study purpose to analyze how the effect of Leader Member Exchange and Career Development on Organizational Citizenship Behavior. This study uses an associative method with a quantitative approach with data collection techniques using a questionnaire. The population in this study were 60 employees of PT Andhika Pratama Jaya Abadi. The data analysis technique used in this study is multiple linear regression analysis techniques. Based on the results of research conducted, it can be concluded that (1) Leader Member Exchange has a significant effect on Organizational Citizenship Behavior. (2) Career Development has a significant effect on Organizational Citizenship Behavior. (3) Leader Member Exchange and Career Development significantly influences Organizational Citizenship Behavior.